FACTORS ASSOCIATED WITH STUDENTS’ PERFORMANCE IN ENGLISH IN THE IMPLEMENTATION OF SPIRAL PROGRESSION - Orbeta, Elden D; Decano, Ronald S (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This sequential exploratory mixed method research design aimed to describe which among language pedagogy, learner attributes, family factor and linguistics environment significantly predicts the performance of students in the English subject in Panabo National High School and thereafter develop a regression model for the study. Factor analysis was employed to develop the instrument derived from the interview of the informants with the use of Creswell (2009) for data analysis. The predictor variables were tested whether these predict the performance of student in English. Using the complete enumeration, 300 respondents were selected to answer the validated and reliable questionnaire. Using Pearson’s r and multiple regression analysis, the figures revealed that language pedagogy, learner attributes, and linguistic environment have significant relationship to the performance of students in English and the emerged themes as factors predict the performance of Grade 10 students in English as well. The multiple regression model of the study is: Grades in English = 0.885(Language Pedagogy) + (– 2.670)(Learner Attributes) + 0.510(Family Factor) + (– 0.171)(Linguistic Environment) + 94.47. The insights gained from the study suggested ways policy and educational initiatives can be crafted to intensify students’ performance in English in the implementation of Spiral progression.